Mitochondrial Drp1 recognizes and induces excessive mPTP opening after hypoxia through BAX-PiC and LRRK2-HK2 - Chenyang Duan; Lei Kuang; Hong Chen; Xinming Xiang; Jiancang Liu; Qinghui Li; Xiaoyong Peng; Yuanqun Zhou; Hongchen Wang; Liangming Liu; Tao Li (2021)
Abstract Mitochondrial mass imbalance is one of the key causes of cardiovascular dysfunction after hypoxia. The activation of dynamin-related protein 1 (Drp1), as well as its mitochondrial translocation, play important roles in the changes of both mitochondrial morphology and mitochondrial functions after hypoxia. However, in addition to mediating mitochondrial fission, whether Drp1 has other regulatory roles in mitochondrial homeostasis after mitochondrial translocation is unknown. In this study, we performed a series of interaction and colocalization assays and found that, after mitochondrial translocation, Drp1 may promote the excessive opening of the mitochondrial permeability transition pore (mPTP) after hypoxia. Firstly, mitochondrial Drp1 maximumly recognizes mPTP channels by binding Bcl-2-associated X protein (BAX) and a phosphate carrier protein (PiC) in the mPTP. Then, leucine-rich repeat serine/threonine-protein kinase 2 (LRRK2) is recruited, whose kinase activity is inhibited by direct binding with mitochondrial Drp1 after hypoxia. Subsequently, the mPTP-related protein hexokinase 2 (HK2) is inactivated at Thr-473 and dissociates from the mitochondrial membrane, ultimately causing structural disruption and overopening of mPTP, which aggravates mitochondrial and cellular dysfunction after hypoxia. Thus, our study interprets the dual direct regulation of mitochondrial Drp1 on mitochondrial morphology and functions after hypoxia and proposes a new mitochondrial fission-independent mechanism for the role of Drp1 after its translocation in hypoxic injury.